PENGARUH RETURN ON ASSETS, LEVERAGE, DAN GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Studi Pada Perusahaan Manufaktur Di Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2013-2015) - Mayang Larasati, 13.05.52.0099; Kartika, Andi (Students' Journal of Accounting and Banking, 2017)
This study examined the effect of the Return On Asset, Leverage / Debt to Equity Ratio, Institutional Ownership, the Board of Independent, Quality Audit and Audit Committee of the Cash Effective Tax Rate. This research was conducted at the Indonesian Stock Exchange by using analysis unit manufacturing consumer goods industry sector. The sampling method using purposive sampling the study period from 2013 to 2015. The relationship between variables or effect described by using multiple linear regression analysis. The results showed that the variable Return On Asset have a negative influence and no significant to tax avoidance, the variable Leverage / Debt to Equity Ratio have a negative influence and no significant to tax avoidance, variable Institutional Ownership have a negative influence and significant effect on tax avoidance, variable the Board of Independent have a positive influence and no significant effect on tax avoidance, variable Quality Audit have a positive influence and significant to tax avoidance, variable Audit Committee have a negative influence and significant tax avoidance.Keywords: Return On Assets, Leverage / Debt to Equity Ratio, Institutional Ownership, Independent Commissioner Board, Quality Audit, The Audit Committee, Cash Effective Tax Rate